PELATIHAN PENGEMBANGAN BAHAN AJAR INTERAKTIF BERBASIS KODULAR BAGI GURU DI SMK TUNAS WIJAYA SURABAYA - wulandari, ruri nurul aeni; Puspasari, Durinda; Trisnawati, Novi (Abimanyu : Jornal of Community Engagement, 2023)
The 2013 revised 2017 curriculum is student-centered and emphasizes students' ability to learn independently, and can communicate information related to the material being studied through a scientific approach as the focus of activities during learning. However, the problem with independent learning is the lack of digital-based teaching materials that can help increase students' understanding, interest, and motivation. The competence of teachers in developing teaching materials that utilize the application of technology is also lacking, so it is necessary to conduct training in the development of codular-interactive teaching materials. The target of this Community Service activity is 20 teachers of the Office Administration and Automation Expertise Program at SMK Tunas Wijaya Surabaya. The results of the codular-based interactive teaching materials training showed that 87% of participants stated that they would apply what they had studied during the training activities into their learning. Keywords: training, development, interactive teaching materials, kodular, teacher